Pancasila-Based Children's Story App: Reading Material for Grade IV Elementary School Students - Decenni Amelia; Isah Cahyani; Kama Abdul Hakam; Cepi Riyana (Al Ibtida: Jurnal Pendidikan Guru MI)
This research aims to develop reading materials story child loaded profile student Pancasila based on mobile application which is a literacy media to help improve interest read students and complement the availability of resources reading which contains the values of the Pancasila lesson profile in story child on the dimension of independence, reasoning critical and creativity as supporters of the independent curriculum. The purpose of this study is to determine the development process and feasibility of products developed using the method study Design & Development. This research was conducted at State Elementary School (SDN) Bahagia 06 Bekasi City, West Java. The subjects of this research were expert material validators, media experts, practitioners and 26 fourth grade students. The research data collection techniques used interviews, observations, and documentation. The instruments used were validator questionnaires and student response questionnaires. as well as teacher response . The developed product was evaluated very well with a percentage of material experts of 96 % in the very feasible category , media experts 94% in the very feasible category, practitioner experts 95% in the very feasible category and student responses were very good. So, from the data obtained, materialreading story child loaded profile student Pancasila based on mobile applications on the dimensions of independence, reasoning critical thinking and creativity are very worthy of being used to help improve interest read students and complement the availability of resources readingwhich contains the values of the Pancasila lesson profile as Supporter curriculum independent.